2012
DOI: 10.1148/radiol.12111327
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel Incoherent Motion and Diffusion-Tensor Imaging in Renal Tissue under Hydration and Furosemide Flow Challenges

Abstract: Purpose:To assess the reproducibility and the distribution of intravoxel incoherent motion (IVIM) and diffusion-tensor (DT) imaging parameters in healthy renal cortex and medulla at baseline and after hydration or furosemide challenges. Materials and Methods:Using an institutional review board-approved HIPAAcompliant protocol with written informed consent, IVIM and DT imaging were performed at 3 T in 10 volunteers before and after water loading or furosemide administration. /msec, P = .0094). Urine output corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
215
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(256 citation statements)
references
References 57 publications
33
215
6
2
Order By: Relevance
“…Additionally, we showed that the f fast2 and f fast3 from the two‐ and three‐component models showed a high and significant correlation with FA from the DTI model. DTI and IVIM are well‐established fitting methods that have been applied in numerous diffusion MRI studies of the kidneys with consistent results,5, 6, 7, 8, 9, 11, 16, 26, 27, 28, 33, 43 which are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, we showed that the f fast2 and f fast3 from the two‐ and three‐component models showed a high and significant correlation with FA from the DTI model. DTI and IVIM are well‐established fitting methods that have been applied in numerous diffusion MRI studies of the kidneys with consistent results,5, 6, 7, 8, 9, 11, 16, 26, 27, 28, 33, 43 which are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…The tractography‐based parameters of all models are most similar to those of the medulla, which is in agreement with the widely accepted belief that diffusion anisotropy originates in the radially oriented structures in the medulla 4, 5, 6, 7, 8, 9, 10, 12, 13, 14, 27. However, tract‐based FA is significantly higher than ROI‐based FA in the medulla.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Good reproducibility of the diffusion parameters (average coefficient of variation [CV] of 3.7 % for cortex and of 5.0 % for the medulla) was reported by Sigmund et al [11]. Wittsack et al [12] reported a dependence of ADC and f p values from the phase of the cardiac cycle proving the influence of the pulsatile blood flow on the evaluation of the parameters in kidneys.…”
Section: Applicationsmentioning
confidence: 87%
“…Hueper et al [18] Yu et al [15] Inci et al [14] Chandarana et al [16] Zhang et al [13] Lu et al [20] Sigmund et al [11] Wittsack et al [12] Rosenkrantz et al [54] Hueper et al [21] ASL Artz et al [26] Pedrosa et al [28] Lanzman et al [29] Rossi et al [27] Cutajar et al [23] Wu et al [24] Boss et al [22] Schor-Bardach et al [30] BOLD Park et al [37] Xiao et al [36] Min et al [38] Yin et al [34] Michaely et al [43] Xin-Long et al [33] Park et al [37] Donati et al [42] Simon-Zoula et al [32] Zhang et al…”
Section: Animal Study Dwi/ Dtimentioning
confidence: 99%